Blood Sample Transportation by Pneumatic Transportation Systems: A Systematic Literature Review. (1st May 2018) - Nybo, Mads; Lund, Merete E; Titlestad, Kjell; Maegaard, Christian U
Abstract: BACKGROUND: Pneumatic transportation systems (PTSs) are increasingly used for transportation of blood samples to the core laboratory. Many studies have investigated the impact of these systems on different types of analyses, but to elucidate whether PTSs in general are safe for transportation of blood samples, existing literature on the subject was systematically assessed. METHODS: A systematic literature review was conducted following the preferred reporting items for systematic reviews and metaanalyses (PRISMA) Statement guidelines to gather studies investigating the impact of PTS on analyses in blood samples. Studies were extracted from PubMed and Embase. The search period ended November 2016. RESULTS: A total of 39 studies were retrieved. Of these, only 12 studies were conducted on inpatients, mainly intensive care unit patients. Blood gases, hematology, and clinical chemistry were well investigated, whereas coagulation, rotational thromboelastometry, and platelet function in acutely ill patients were addressed by only 1 study each. Only a few parameters were affected in a clinically significant way (clotting time parameter in extrinsic system thromboelastometry, pO2 in blood gas, multiplate analysis, and the hemolysis index). CONCLUSIONS: Owing to their high degree of heterogeneity, the retrieved studies were unable to supply evidence for the safety of using PTSs for blood sample transportation. In consequence, laboratories need to measure and document the actual acceleration forces in their existing PTS, instituting quality target thresholds for these measurements such as acceleration vector sums. Computer modeling might be applied to the evaluation of future PTS installations. With the increasing use of PTS, a harmonized, international recommendation on this topic is warranted.